Motility performance of thawed spermatozoa of bulls from the tropics throughout the year - Poclín Rojas, Annie Yoselin (2025)
Under tropical conditions, seasonal variations may also influence the sperm characteristics of Bos indicus. The objective was to evaluate the motility of thawed sperm of bulls from the Peruvian tropics throughout the year. Over 24 months, 129 ejaculates were evaluated based on semen quality and subjected to slow horizontal freezing in 0.5 mL straws. After thawing, the individual, seasonal period, and season effect on motility and kinetic parameters were analyzed using a Sperm Class Analyzer® (Microptic S.L.U., Barcelona, Spain). There was an individual effect on volume, motility, fresh concentration, and kinetic parameters when thawed. In the dry period, higher straight-line velocity (VSL) (p < 0.05) and beat cross frequency (BCF) were found than in the rainy period (p < 0.01). In summer and autumn, there was greater total motility, fast, circular routes, curvilinear velocity, average path velocity, VSL, amplitude of lateral displacement of the head, and BCF (p < 0.01). Greater volume and motility were found in winter and spring, but in summer and autumn, greater speed and vigor of movement were obtained in thawed sperm. The variation in annual climate patterns influences the seminal quality of bulls, and its effect needs to be assessed to propose adaptation strategies to climate change in tropical areas.